Evaluasi Kecukupan Panas Proses Pasteurisasi Nata de Coco dalam Kemasan Plastik Polietilen - Hafzialman Hafzialman; Feri Kusnandar; Eko Hari Purnomo (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
Sliced nata de coco in light syrup is categorized as an acidified food with an equilibrium pH of 3.3-3.9. Hence, pasteurization process can be applied to kill potential pathogenic and spoilage microorganims in order to produce a safe product and extend its shelf life. The objective of this study was to evaluate the thermal processing adequacy of sliced nata de coco in light syrup (net weight: 2 kg per package; size per slice: 15x15x15 mm2) packed in polyethylene plastic bag (320x230x0.16 mm3) and pasteurized in a conveyor pasteurizer at a heating temperature of 98+2oC for 20 minutes. Thermal process adequacy was determined by comparing the pasteurization value (P) of the process with a standardized P80 value at different D cycles for some microbial targets (2D80, 3D80 and 6D80). The designed pasteurization process satisfactorily inactivated vegetative cells, mold, yeast, Bacillus coagulans, Byssochlamus fulva, and Byssochlamus fulva nivea (Pvalue >P80 value). However, the thermal process was not sufficient to inactivate Alicyclobacillus acidoterrestris, Bacillus polymyxa, Bacillus macerans dan Bacillus pasteurianum (Pvalue<P80 value).